Power in the flow: how menstrual experiences shape women's strength training performance - Ryman Augustsson, Sofia; Findhé-Malenica, Anna (Frontiers in Sports and Active Living, 2025)
IntroductionHormone levels fluctuate significantly throughout the menstrual cycle (MC), potentially impacting physical performance during training. However, the number of studies examining women's experiences during strength training throughout the MC is limited. Therefore, the aim of this study was to explore women's perceptions of strength training during different MC phases.MethodsIn this study, a qualitative study design was used where five women (24–32 years) with recreational experience in strength training kept an exercise diary during a MC. Data were collected using semi-structured interviews and analyzed using qualitative conventional content analysis, with an inductive approach.ResultsFrom the analysis, three overarching themes describing the content of the interviews emerged: “Biopsychosocial Dynamics and Individual Variability in the Early Follicular Phase”, “From Peak to Breaking Point: Performance Dynamics from Late Follicular Phase to Ovulation” and “Diversity in Mental and Physical Well-Being During the Luteal Phase”. From women's perspectives, strength training performance seems to fluctuate across the different phases of the MC, influenced by both physiological and psychological challenges, though with individual variation.DiscussionThe findings highlight the need for a holistic approach to managing the physiological and psychological challenges that may arise during each phase of the MC, along with the importance of social support. The results also stress that performance fluctuations across the MC are unique, further emphasizing the inability to recommend general phase-based exercise protocols.